Home ownership beyond asset and security : perceptions of housing related security and insecurity in eight European countries - Elsinga, Marja (Housing and urban policy studies, 2007)
Offers information by linking developments on home ownership with developments in the financial and labor markets in the context of globalization. This book is the conclusion of a body of research that started with a workshop held at the University of York in October 2000, and which resulted in the book "Globalisation and Home Ownership."